2016
DOI: 10.2147/dddt.s112723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pramipexole dose–response relationships in Parkinson's disease

Abstract: BackgroundPramipexole (PPX), a non-ergot dopamine receptor agonist, is a first-line treatment for Parkinson’s disease (PD). A critical dose level above which a better benefit-to-harm ratio exists has not been examined.MethodsChinese PD patients (n=464) were retrospectively analyzed by PPX maintenance dose, PD stage, combined levodopa dose, and baseline tremor contribution. The sum score of Baseline Activities of Daily Living (part II) and Motor Examination (III) of the Unified Parkinson’s Disease Rating Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…6 Through a neuroprotective effect, pramipexole delays levodopa-induced motor complications in early PD, controls motor symptoms, and relieves depression in PD patients. 7 A recent study demonstrated that inflammatory cytokines are abnormally expressed in patients with neurodegenerative diseases and are involved in disease development. 8 Another study found that long-term overactivation of microglial cells in the brains of PD patients was associated with significantly increased levels of a large number of pro-inflammatory cytokines, including tumor necrosis factor (TNF)-a, interleukin (IL)-1b, IL-6, and interferon-c. 9 Although the outcomes of treatment with either pramipexole or levodopa alone for PD have been widely studied, the effect of combining pramipexole with levodopa on inflammatory cytokines and disease outcomes has not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…6 Through a neuroprotective effect, pramipexole delays levodopa-induced motor complications in early PD, controls motor symptoms, and relieves depression in PD patients. 7 A recent study demonstrated that inflammatory cytokines are abnormally expressed in patients with neurodegenerative diseases and are involved in disease development. 8 Another study found that long-term overactivation of microglial cells in the brains of PD patients was associated with significantly increased levels of a large number of pro-inflammatory cytokines, including tumor necrosis factor (TNF)-a, interleukin (IL)-1b, IL-6, and interferon-c. 9 Although the outcomes of treatment with either pramipexole or levodopa alone for PD have been widely studied, the effect of combining pramipexole with levodopa on inflammatory cytokines and disease outcomes has not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…After 3-years of treatment, in the same manner, motor and daily living tasks (UPDRS III scale) of the patients of PP cohort were also improved. The study results were parallel with the results of double-blind studies (11,12). Pramipexole may also delay the progression of disease in patients with confirmed Parkinson's disease.…”
Section: Expendituresupporting
confidence: 66%
“…Our analysis found significant improvement in QoL among those who received the optimal maintenance dose of pramipexole (≥ 1.5 mg). Pramipexole 1.5 mg was determined as a critical dose since patients receiving ≥ 1.5 mg per day showed greater improvements in motor function and fewer adverse events than patients who received < 1.5 mg per day [ 21 ]. However, a daily dose lower than 1.5 mg has been reported in a previous clinical trial in China [ 40 ] and this remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Additional exploratory subgroup meta-analyses were conducted after grouping selected studies according to: (i) pramipexole treatment dose: studies with ≥ 80% of patients receiving the recommended daily dose of ≥ 1.5 mg were categorised as “optimal dose” groups [ 20 , 21 ] and those with a daily dose < 1.5 mg were considered “low dose” groups; (ii) baseline disease stage: advanced or early PD, according to the disease severity of the respective original studies; (iii) baseline QoL level: the studies were grouped into high (≥ 25) or low (< 25) QoL groups according to the baseline total PDQ-39 mean scores.…”
Section: Methodsmentioning
confidence: 99%